2017
DOI: 10.1007/s00330-017-4807-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of posterior fossa and brain morphology after in utero repair of open neural tube defects assessed by MRI

Abstract: • Hindbrain herniation is significantly more pronounced in myeloschisis than in myelomeningocele • Resolution of hindbrain herniation 4 weeks after in utero closure of ONTD • MRI is valuable for preoperative assessment and postoperative evaluation following in utero repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
8
45
0
Order By: Relevance
“…Our sonographic data regarding HH reversal in 96 % of cases after fMMC repair is underlined by the study published on MR imaging by Retmann et al with the first 27 cases that underwent fMMC repair at the Zurich Centre for fetal Diagnosis and Therapy, also showing a resolution of the HH in 96 % of cases [18]. Other authors have shown MRI data demonstrating that HH improves or reverses in 80-96 % of cases after open fMMC repair [5,7,19,20].…”
Section: Discussionsupporting
confidence: 67%
“…Our sonographic data regarding HH reversal in 96 % of cases after fMMC repair is underlined by the study published on MR imaging by Retmann et al with the first 27 cases that underwent fMMC repair at the Zurich Centre for fetal Diagnosis and Therapy, also showing a resolution of the HH in 96 % of cases [18]. Other authors have shown MRI data demonstrating that HH improves or reverses in 80-96 % of cases after open fMMC repair [5,7,19,20].…”
Section: Discussionsupporting
confidence: 67%
“…37,38,57,58 For instance, in our own current experience of 65 cases, we had only one patient with mild pulmonary edema (1.5%, MOMS 6%) and no patient requiring transfusion at delivery (MOMS 9%). Further, in our cohort, a higher rate of complete resolution of hindbrain herniation (over 90%) 59 (MOMS 36%), and a higher median gestational age at birth have been noted. 60 In addition, a different tocolysis management has led to markedly less side effects without compromising uterine efficacy.…”
Section: Diagnostic Workup and Eligibility For Prenatal Osb Repairsupporting
confidence: 52%
“…Occlusion of CSF flow outlets of the fourth ventricle and impairment of the CSF circulation at the craniocervical junction can result in obstructive hydrocephalus [12]. Dysplastic tectal plate, commonly demonstrated in Chiari II patients, may be associated with cerebral aqueduct stenosis [3]. Hypoplastic posterior cranial fossa and cerebellar herniation can also decrease cerebral venous outflow, which might thus impair CSF absorption and result in a component of communicating hydrocephalus [12].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the rhombencephalic vesicle including the developing fourth ventricle fails to expand and a small posterior fossa evolves. Indeed, intrauterine repair of the open spinal dysraphism has been shown to result in the improvement of the posterior fossa deformity [2,3]. Although the hallmark of Chiari II malformation is a small posterior fossa, supratentorial abnormalities, such as periventricular nodular heterotopia and callosal dysgenesis, are not uncommon [4], possibly related to the impairment of neuronal migration and axonal guidance by altered CSF hydrodynamics [5].…”
Section: Introductionmentioning
confidence: 99%